Perilaku Pengikutan dan Efisiensi Pasar Saham - Setiyono, Setiyono ([Yogyakarta] : Universitas Gadjah Mada, 2011)
This paper analyzed institutional trading activities with intraday data of trade from 2003 through 2005 to determine whether the institutional traders herd when they trade stocks, and to examine its impact on both subsequent stock prices and stock market efficiency. This study found the existence of institutional herding, on the avemge the intensity is about 8,4 percent and much higher intensity are found on sell than buy side. It is not clearly found they prefer to buy both smallest and largest stocks and trade lower risk stocks. Weak evidence is also found that they followed both positive-feedback and negative-feedback trading strategy. Their behavior did not clearly affect price reversaJ because abnormal returns are found non monotonically in subsequent period. This research also found that the existence of intitutional herding can increase stock market efficiency. Positive effect of the herding on market efficiency can increase conditional on the occurance of large block trade and block trade initiated by buyers. Result of this researh provides justification of the general view that herdi